13C Metabolic Flux Analysis of Escherichia coli Engineered for Gamma‐Aminobutyrate Production. Issue 6 (7th May 2020) - Im, Dae‐Kyun; Hong, Jaeseung; Gu, Boncheol; Sung, Changmin; Oh, Min‐Kyu
Abstract: Escherichia coli is engineered for γ‐aminobutyrate (GABA) production in glucose minimal medium. For this, overexpression of mutant glutamate decarboxylase (GadB) and mutant glutamate/GABA antiporter (GadC), as well as deletion of GABA transaminase (GabT), are accomplished. In addition, the carbon flux to the tricarboxylic acid cycle is engineered by the overexpression of gltA, ppc, or both. The overexpression of citrate synthase (CS), encoded by gltA, increases GABA productivity, as expected. Meanwhile, the overexpression of phosphoenolpyruvate carboxylase (PPC) causes a decrease in the rate of glucose uptake, resulting in a decrease in GABA production. The phenotypes of the strains are characterized by 13 C metabolic flux analysis ( 13 C MFA). The results reveal that CS overexpression increases glycolysis and anaplerotic reaction rates, as well as the citrate synthesis rate, while PPC overexpression causes little changes in metabolic fluxes, but reduces glucose uptake rate. The engineered strain produces 1.2 g L −1 of GABA from glucose. Thus, by using 13 C MFA, important information is obtained for designing metabolically engineered strains for efficient GABA production. Abstract : 13 C Metabolic flux analysis (MFA) can help metabolic engineering since it can provide an information for metabolic modification target. In this work, authors produce γ‐aminobutyrate (GABA) from engineered Escherichia coli . Tricarboxylic acid (TCA) cycle is modified by overexpressing citrate synthase or phosphoenolpyruvate carboxylase to enhance GABA productivity and 13 C MFA can characterize perturbated flux of engineered mutants. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visit www.afob.org